2021
DOI: 10.3389/fmicb.2020.596472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Different Sugarcane Cultivars on Rhizosphere Bacterial Communities of Sugarcane and Soybean Upon Intercropping

Abstract: Intercropping of soybean and sugarcane is an important strategy to promote sustainable development of the sugarcane industry. In fact, our understanding of the interaction between the rhizosphere and bacterial communities in the intercropping system is still evolving; particularly, the influence of different sugarcane varieties on rhizosphere bacterial communities in the intercropping process with soybean, still needs further research. Here, we evaluated the response of sugarcane varieties ZZ1 and ZZ9 to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 98 publications
(110 reference statements)
3
25
0
Order By: Relevance
“…In intercropping, biodiversity and structure of rhizosphere bacterial community of plant species/cultivars did not differ significantly from sole cropping in any of the two experiments ( Figure 1 ). This is consistent with previous reports made on wheat-fababean IC ( Tang et al, 2016 ) and on sugarcane varieties IC ( Liu et al, 2021 ). Differences between intercropping and sole cropping were only detected in pea, when pooling data from the two experiments.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In intercropping, biodiversity and structure of rhizosphere bacterial community of plant species/cultivars did not differ significantly from sole cropping in any of the two experiments ( Figure 1 ). This is consistent with previous reports made on wheat-fababean IC ( Tang et al, 2016 ) and on sugarcane varieties IC ( Liu et al, 2021 ). Differences between intercropping and sole cropping were only detected in pea, when pooling data from the two experiments.…”
Section: Discussionsupporting
confidence: 94%
“…Concerning IC co-occurrence network, Tang et al (2021) showed, through a shotgun metagenome analysis, that sugarcane and peanut IC increased the abundance of bacterial genes involved in organic matter turnover comparing to SC, without correlating these differences to changes in microbiota diversity. Liu et al (2021) showed differences between the co-occurrence networks between two sugarcane varieties in IC. None of these studies analyzed the differences in co-occurring network between bacterial taxa in IC and SC.These complex interactions may account for the increased yield of the IC but also of the following crop, indicating a positive legacy effect of multispecies cropping systems (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations